Code-Based Document Authentication Using SHA-3 and McEliece - Vadillatul Ni'ma Maulidya; Muhammad Khudzaifah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Personal data protection is essential to ensure the security and authenticity of digital documents. One approach to achieving document authenticity is through a code-based document authentication mechanism. This study proposes a document authentication scheme using the SHA-3 hash function combined with the McEliece code-based cryptosystem with Hamming code. The authentication process begins by hashing the document content using SHA-3 to generate a message digest. The resulting hash value is converted into binary form and then encoded and encrypted using the public key of the McEliece cryptosystem, producing an authentication code. During the verification phase, the received authentication code is processed through the decoding mechanism using the private key, allowing error correction and recovery of the original hash representation. A document is considered authentic if the decoded hash matches the hash value generated from the received document. Experimental results show that the authentication code depends on the McEliece key pair used, ensuring uniqueness and resistance to forgery. Furthermore, the combination of SHA-3 and the McEliece cryptosystem exhibits an Avalanche Effect close to 50%, indicating strong diffusion properties. These results demonstrate that the proposed code-based authentication scheme provides a reliable cryptographic solution for ensuring the authenticity and protection of digital documents, particularly against future cryptanalytic threats.